2020
DOI: 10.21203/rs.2.10786/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality among children under five years admitted for routine care of severe acute malnutrition: a prospective cohort study from Kampala, Uganda

Abstract: Background Mortality among children under five years of age admitted to malnutrition units in sub-Saharan Africa remains high. The burden of HIV infection, a major risk factor for mortality among patients with severe acute malnutrition (SAM), has reduced due to concerted prevention and treatment strategies. None the less, anecdotal reports from the malnutrition unit at Uganda’s National Referral Hospital (NRH) indicate that there is high mortality among patients with severe acute malnutrition (SAM) in routine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…This nding is consistent with studies done, in Uganda (14), in Egypt (27) and studies conducted in Ethiopia, Jimma university (17), Gondar university (4) and Gedio Zone (28). On the other hand, this nding is lower than a study done in South Africa (12) and other study in Uganda (15). The discrepancy might be due to high proportion of HIV positive cases, in South Africa, 43% were HIV infected and this in turn increases the mortality due to the complexity of the management and opportunist infections.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This nding is consistent with studies done, in Uganda (14), in Egypt (27) and studies conducted in Ethiopia, Jimma university (17), Gondar university (4) and Gedio Zone (28). On the other hand, this nding is lower than a study done in South Africa (12) and other study in Uganda (15). The discrepancy might be due to high proportion of HIV positive cases, in South Africa, 43% were HIV infected and this in turn increases the mortality due to the complexity of the management and opportunist infections.…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to the difference in methodology which was a prospective cohort in the previous study. As a result, it included patients discharge following against medical advice and prior co-morbidities, for example in Uganda of the children were HIVinfected (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across traits, the differences in PRS accuracy across cohorts but within the same ancestry are much smaller than the differences across ancestries but within the UK Biobank, indicating that ancestry has a larger impact on genetic risk prediction than cross-cohort differences analyzed here. Smaller effects on genetic prediction accuracy differences across cohorts may be attributable to environmental differences, such as higher rates of malnutrition and infectious diseases previously reported in Uganda and in the GPC (Asiki et al, 2013; Nalwanga et al, 2020).…”
Section: Resultsmentioning
confidence: 90%
“…The mortality rate due to SAM in Sub-Saharan Africa ranges from 9.8 to 46% [11][12][13][14]. Evidences indicated that the likely cause of high mortality rate could be HIV infection [11,15], lack of appetite, chest in drawing [14], co-morbidities and altered consciousness at admission [13,16].…”
Section: Introductionmentioning
confidence: 99%